Pengaruh Penerapan Strategi Pembelajaran Index Card Match terhadap Prestasi Hasil Belajar Siswa pada Mata Pelajaran Aqidah Akhlak - Saifudin; Salma Avinia; Fatmawati Norma Sari (IBTIDA, 2020)
The lack of learning media used by teachers in delivering material. Besides that the learning methods used by teachers are still conventional or lecture. So we need one of the learning strategies that can be used, namely the Index Card Match learning strategy. This study aims to determine the effect of learning Index Match cards on the learning outcomes of fifth grade MI students. This type of research is quantitative with correlational research designs. Methods of collecting observational data, questionnaires and documentation. Data analysis using Product Moment Correlation. The results of this study are 1) The implementation of the Index Card Match learning strategy in the high category there are 15 respondents with a percentage of 60%, then in the medium category there are 10 respondents with a percentage of 40%, and those included in the low category there are no respondents with a percentage of 0%. 2) Student achievement in Aqidah Morals in the high category there are 7 students with a percentage of 28%, then in the medium category there are 13 students with a percentage of 52%, and those included in the low category there are 5 students with a percentage of 20%. 3) There is an effect of the application of the Index Card Match learning strategy to the learning achievement of Aqeedah Moral students in class V MI. This is based on the analysis results obtained r = 0.597 then consulted with r table at a significant level of 5% and N = 25 is 0.396 so that r count is greater than r table that is 0.597> 0.396 which means there is an influence. The level of influence is strong, because the analysis results obtained value of r_xy = 0.597 if consulted with Sugiono's interpretation is between 0.40-0.599, which means it is moderate.